Comparison of different mobile health applications for intervention in children and adolescent with overweight: a protocol for systematic review with meta-analysis and trial sequential analysis. Issue 12 (7th December 2020) - Perego, Paolo; Rashid, Rajeeb; Gluud, Christian; Jakobsen, Janus C; Andreoni, Giuseppe; Lissau, Inge
Abstract : Introduction: Overweight in children is increasing worldwide. Innovative smartphone health applications (mHealth apps) have either sought to deliver single or multi-component interventions for the management of overweight in children. However, the clinical effects of these apps are poorly explored. The objective of the review will be to compare the benefits and harms of different categories of mHealth apps for intervention of overweight in children. Methods and analysis: We will include randomised clinical trials irrespective of publication type, year, status or language. Children and adolescents between 0 to 18 years will be referred to as children in the remaining part of the paper. Children with all degrees of overweight included obesity and morbidly obese in the remaining part of the paper will be referred to as overweight. We plan to classify different apps according to type of intervention, measurement device, coaching and reward system. The following databases will be used: Cochrane Library, Excerpta Medica database (Embase), PsycINFO, PubMed, IEEE Explore and Web of Science, CINAHL and LILACS. Primary outcomes will be body mass index z-score, quality of life and serious adverse event. Secondary outcomes will be body weight, self-efficacy, anxiety, depression and adverse event not considered serious. Study inclusion, data extraction and bias risk assessment will be conducted independently by at least two authors. We will assess the risk of bias through eight domains and control risks of random errors with Trial Sequential Analysis. The quality of the evidence will be assessed using Grading of Recommendations Assessment, Development and Evaluation Tool (GRADE). Ethics and dissemination: As the protocol is for a systematic reviews, we have not included any patient data and we do not require ethical approval. This review will be published in a peer-reviewed journal. PROSPERO registration number: CRD42019120266.